2007
DOI: 10.1039/b708116b
|View full text |Cite
|
Sign up to set email alerts
|

Dithioacetalisation of PEEK: a general technique for the solubilisation and characterisation of semi-crystalline aromatic polyketones

Abstract: The family of semi-crystalline, aromatic, high-temperature thermoplastics known as poly(ether-ketone)s are insoluble in conventional organic solvents, but undergo completely general and quantitatively reversible reactions with alkanedithiols in strong acid media, to give soluble poly(dithioacetal)s, which are readily characterisable by GPC and light scattering techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
(6 reference statements)
0
19
0
Order By: Relevance
“…Turner and colleagues and Colquhoun et al . had previously reported studies on the structure and molecular weight respectively of insoluble polyetheretherketone (PEEK) by MALDI‐TOF, wherein soluble PEEK oligomers or soluble modified PEEK derivative‐like poly(ether dithioketal) were used as the model . However, the appropriate models of 10a have not been found so far for structure analysis because the MALDI‐TOF technique favors the ionization of soluble low molecular weight species .…”
Section: Resultsmentioning
confidence: 99%
“…Turner and colleagues and Colquhoun et al . had previously reported studies on the structure and molecular weight respectively of insoluble polyetheretherketone (PEEK) by MALDI‐TOF, wherein soluble PEEK oligomers or soluble modified PEEK derivative‐like poly(ether dithioketal) were used as the model . However, the appropriate models of 10a have not been found so far for structure analysis because the MALDI‐TOF technique favors the ionization of soluble low molecular weight species .…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary studies showed that prolonged reactions (18)(19)(20) Analysis of poly(ether ketal)s by 1 H NMR spectroscopy showed no detectable dithioketal residues, but deprotected ketonic units were present at levels of between 5 and 45 mole%. Both PEEK-1,3-dithiolane (1) and PEEK-1,3-dithiane (2) successfully participated in this reaction, forming the same end-products.…”
Section: Reactions Of Peek Dithioketals With Ethane-12-diolmentioning
confidence: 99%
“…9-14 Amongst the first efforts was that of Kelsey et al, 14 With specific relevance to the present work, a further novel approach to fully-reversible derivatisation of poly(arylene ether ketone)s has been reported. 18,19,20 The carbonyl groups were protected by reaction with dithiols such as 1, The dithioketalization approach offers a general, non-degradative pathway for reversible chemical modification of any poly(arylene ether ketone). However, removal of the dithioketal group is generally slow and difficult (though achievable), 19 chemistry, cyclic dithioketals are also difficult to hydrolyze but they do participate in exchange reactions, for example with ethane-1,2-diol or 2-mercaptoethanol in the presence of a catalyst such as mercury(II) chloride, yielding the corresponding 1,3-dioxolanes or 1,3-oxathiolanes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, aliphatic PK is a semicrystalline thermoplastic that exhibits superior mechanical properties, barrier properties, and high temperature and chemical resistance. Due to these characteristics, aliphatic PK can be used for various applications, such as barrier packaging, engineering, and as fiber . However, despite its high thermal stability, the combustibility of aliphatic PK restricts its applications.…”
Section: Introductionmentioning
confidence: 99%